Os fundamentos ontológicos da ética e as suas configurações no debate teórico do serviço social: um estudo introdutório a partir de György Lukács - Santos, Débora Rodrigues (2014)
This dissertation focuses the ethics and aims to investigate it from their ontological and historical materialist ontological sense in fundamentals as well as the settings in the debate of Social Work. The perspective adopted here is based on the Marxian theory based on the contribution of Lukacs (2013). The research was eminently theoretical. This is classified as exploratory and was through two methodological stages: from the literature and theoretical research, which developed into four chapters. In Chapter I, we conducted a survey on "Origins, historical trajectory of ethics and its philosophical foundations" according to the analysis of Sidgwick (2010). Study "The ontological- material bases of Ethics "in Chapter II, we present the ontological genesis of ethics from alternative and value, bringing us Lukacsian the following categories: work, teleology, causality, objectivity, externalizing, and alternative must-be. The following chapters present "Social Work and Ethics "by their relationships, primarily through ethical and philosophical expressions contained in the Codes of Professional Ethics. We conclude that the professional ethics of social work has advanced significantly, however has several challenges, including the pressing need to increase knowledge of the materialist ontological genesis of ethics. In this direction, our research brought contribute to the formation and exercise professionals. Given the introductory nature of this study, we emphasize that the results should be seen as initial findings that point to future thoughtful reflections of the difficult topic of ethics complex.